THE AUTHORITY OF REGIONAL GOVERNMENTS IN PROVIDING ENVIRONMENTAL PROTECTION, MANAGEMENT, AND LAW ENFORCEMENT - Achmad Alif Nubani; Mirza Agung Rahmatullah (PT. Jurnal Center Indonesia Publisher, 2026)
The authority of local governments in environmental protection, management, and law enforcement is exercised within the framework of regional autonomy in Indonesia. Under Law Number 23 of 2014 and Law Number 32 of 2009, environmental affairs have been decentralized as mandatory governmental functions under the authority of provincial and regency/municipal governments. This study employs a normative juridical research method, utilizing secondary data in the form of statutory regulations and legal literature. The findings indicate that regional autonomy provides local governments with greater capacity to understand and respond to the objective environmental conditions of their respective regions. Environmental law enforcement is implemented through administrative sanctions, criminal sanctions, and civil liability based on the principle of strict liability. The role of local governments is therefore crucial in ensuring the sustainability of environmental functions and in safeguarding community welfare through effective environmental governance.